Exchange rates, capital flows and policy - Sinclair, P. J. N.; Driver, Rebecca; Thoenissen, C. (Routledge international studies in money and banking ;, 2005)
Combining thorough scholarship with illuminating real-world examples, this edited collection provides insights on the causes and consequences of movements in both exchange rates and external assets and has a strong focus on the policy implications of operating in an open economy, particularly the choice of exchange rate and monetary policy, exchange rate intervention and policies on capital mobility.